JAMI AND NAVOI: ON THE ISSUE OF CREATIVE INFLUENCE - Ismoilov, Ilyos (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The study of transition of motifs and plots in literary criticism, that is, the study of the transportation of plots, has taken a serious turn since the 19th century. The theory of transportation of plots, outlined by T. Benfey, showed that the source of multiple plots in European storytelling is the “Panchatantra”, which contains ancient Indian parables and tales. According to T. Benfey, it is precisely creative appropriation or transportation as an inter-literary connection that is the driving force behind literary development. The task of specialists is to clarify these appropriations and connections. It should be noted that the theme of Alexander has also been transformed over the centuries from West to East, from history to literature. In this process, it underwent certain changes, but it was able to preserve its basic motifs. By acquiring a mobile character, this theme also served as a literary and aesthetic tool that created and manifested inter-literary connections. In the history of this theme, epics within the tradition of epic poetry appear to be a large and important link. In this article, The Iskandarnamas of Abdurahman Jami and Alisher Navoi are comparatively analyzed. The main focus is on the issues of creative cooperation, creative consensus, and creative influence. All opinions and considerations are proved by the examples of the epics "Khiradnamai Iskandari" and "Saddi Iskandari".
Keywords: Abdurahman Jami; Alisher Navoi; comparative studies; Iskandar; Iskandarnama; creative influence; literary cooperation